ACVR2B/Fc counteracts chemotherapy-induced loss of muscle and bone mass. Issue 1 (December 2017) - Barreto, Rafael; Kitase, Yukiko; Matsumoto, Tsutomu; Pin, Fabrizio; Colston, Kyra; Couch, Katherine; O'Connell, Thomas; Couch, Marion; Bonewald, Lynda; Bonetto, Andrea
Abstract Chemotherapy promotes the development of cachexia, a debilitating condition characterized by muscle and fat loss. ACVR2B/Fc, an inhibitor of the Activin Receptor 2B signaling, has been shown to preserve muscle mass and prolong survival in tumor hosts, and to increase bone mass in models of osteogenesis imperfecta and muscular dystrophy. We compared the effects of ACVR2B/Fc on muscle and bone mass in mice exposed to Folfiri. In addition to impairing muscle mass and function, Folfiri had severe negative effects on bone, as shown by reduced trabecular bone volume fraction (BV/TV), thickness (Tb.Th), number (Tb.N), connectivity density (Conn.Dn), and by increased separation (Tb.Sp) in trabecular bone of the femur and vertebra. ACVR2B/Fc prevented the loss of muscle mass and strength, and the loss of trabecular bone in femurs and vertebrae following Folfiri administration. Neither Folfiri nor ACVR2B/Fc had effects on femoral cortical bone, as shown by unchanged cortical bone volume fraction (Ct.BV/TV), thickness (Ct.Th) and porosity. Our results suggest that Folfiri is responsible for concomitant muscle and bone degeneration, and that ACVR2B/Fc prevents these derangements. Future studies are required to determine if the same protective effects are observed in combination with other anticancer regimens or in the presence of cancer.